Effect of Nitrogen and Potassium Fertilization on Vegetative Growth, Yield and Sugar Content of Two Sweet Sorghum (Sorghum bicolor L. Moench) Genotypes (University of Khartoum Journal of Agricultural Sciences, 2021)
This experiment was conducted at the Demonstration Farm of the Faculty of Agriculture University of Khartoum at Shambat, Sudan, in 2016. The aim of the experiment was to study the effect of nitrogen and potassium fertilization on growth, yield and sugar content of two genotypes of sweet sorghum (Sorghum bicolor L. Moench). The treatments consisted of three levels of nitrogen (0; 50 and 100 kg N/Fed), potassium (0; 50 and 100 kg K/Fed) and two sweet sorghum genotypes;G1, RNF 1107 white colored seeds from El Gazira Aba and G2, El Banjadeed, black colored seeds from Kordofan. The experiment was arranged in a randomized complete block design with three replications. Studied parameters were plant height, number of leaves, leaf area, stem diameter, plant, leaf, stem and head fresh weights, baggasse and juice weights. The results showed that nitrogen application had a significant (P≤0.05) effect on plant height, number of leaves per plant, leaf area, stem diameter, plant and leaves' fresh weight, baggasse and juice weights. Potassium application affected plant height significantly (P≤0.05) but had no significant (P≤0.05) effect on number of leaves per plant, leaf area and stem diameter. Also potassium application had no significant effect on all studied yield parameters. The results indicated significant (P≤0.05) differences for most interactions. G2 showed better performance than G1 for plant height, leaf number, leaf area, stem diameter and yield parameters at N1K1
Keywords: sorghum; fertilization; nitrogen; potassium; Sudan